FRODO'S LOYALTY REFLECTED IN PETER JACKSON'S THE LORD OF THE RINGS TRILOGY (2001-2003): AN INDIVIDUAL PSYCHOLOGICAL APPROACH - HANDAYANI , CATUR SRI (2010)
The major problem of this study is to know how does Frodo's loyalty to keep the ring until it is destroyed reflected in The Lord of the Rings. The objectives of the study are: to expose the Frodo Baggins' loyalty based on the individual psychological approach by Alfred Adler. In concluding this study, the researcher uses qualitative research, in which the primary data is The Lord of the Rings movie, and the secondary data is the other data related to the research such as some books of Individual Psychological theories, script of the movie, internet and other relevant information. The study comes to the following conclusions, first, based on the structural analysis of each element; it shows that the narrative elements such as character and characterization, setting, plot, point of view, and theme are related to each other, technical elements such as mise-en-scene, cinematography, sound, editing form the unity into good quality of movie. Second, based on the individual psychological analysis, there is close relation between the movie production and the psychology reality underlying it, such as the mental condition of major character to keep his loyalty for bringing the ring of evil in order to be not taken by enemies.